Afraid to Talk? Exploring Arabic Speaking Anxiety among University Students - Achmad, Septiana Azhar Anugrainy; Gadoum, Hamida; Bahauddin, Muhammad Hadzik; Ma'arij, Mahbub; Tusilo M., Ahmad; Elfadhly, Zakly Zola (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
This study aims to identify the levels and influencing factors of foreign language anxiety in Arabic Language learning among students at Tribakti of Islamic University. The study involved 73 participants and employed the Foreign Language Classroom Anxiety Scale (FLACS) developed by Horwitz et al. as the main instrument. The findings reveal that most learners experience mild levels of anxiety, while others report moderate to high anxiety levels. These results align with the perspectives of Krashen, Horwitz, MacIntyre, and Liu, who emphasize that anxiety is a key affective variable that can hinder input comprehension, affect language processing, and reduce learners’ confidence, particularly in speaking. This study enriches the literature on foreign language anxiety within the context of Arabic language learning, an area still less explored compared to other foreign languages. Additionally, it offers practical recommendations for educators, encouraging the adaptation of emotionally supportive teaching approaches, including anxiety-reduction strategies and confidence-building interventions to enhance learning outcomes.